Exploring Students' Perspectives on the benefits of applying Video learning materials in class in Improving Listening Skills - Mega Silvia Putri; Rakhmawati Rakhmawati; Lilik Mahmudah (TELL - US JOURNAL, 2025)
This article discusses students' perspectives on the benefits of using video learning materials in the classroom to improve listening skills. By gathering students' views and experiences, this study identifies how video materials can increase engagement, understanding, and information retention. Through qualitative analysis, the findings show that the use of videos not only makes learning more interesting but also helps students overcome challenges in understanding various accents and intonations. This article aims to provide insights into the potential of video as an effective learning tool and its implications for developing essential listening skills in academic and everyday communication contexts. Therefore, this study is expected to contribute to more innovative teaching practices that are responsive to students' needs.